Rational backbone redesign of a fructosyl peptide oxidase to widen its active site access tunnel. Issue 12 (9th September 2020) - Rigoldi, Federica; Donini, Stefano; Torretta, Archimede; Carbone, Anna; Redaelli, Alberto; Bandiera, Tiziano; Parisini, Emilio; Gautieri, Alfonso
Abstract: Fructosyl peptide oxidases (FPOXs) are enzymes currently used in enzymatic assays to measure the concentration of glycated hemoglobin and albumin in blood samples, which serve as biomarkers of diabetes. However, since FPOX are unable to work directly on glycated proteins, current enzymatic assays are based on a preliminary proteolytic digestion of the target proteins. Herein, to improve the speed and costs of the enzymatic assays for diabetes testing, we applied a rational design approach to engineer a novel enzyme with a wider access tunnel to the catalytic site, using a combination of Rosetta design and molecular dynamics simulations. Our final design, L3_35A, shows a significantly wider and shorter access tunnel, resulting from the deletion of five‐amino acids lining the gate structures and from a total of 35 point mutations relative to the wild‐type (WT) enzyme. Indeed, upon experimental testing, our engineered enzyme shows good structural stability and maintains significant activity relative to the WT. Abstract : Using a rational in silico design and screening method, we produced an engineered fructosyl peptide oxidase featuring a wider catalytic site access tunnel, without compromising its global fold and catalytic function. The design involved remodeling of the backbone structure of the enzyme, a feature that is not possible with conventional enzyme engineering techniques. Our engineered enzyme represents a possible starting point for the development of improved biosensors for the monitoring of diabetes.